Una poética del desarraigo en "Los detectives salvajes" y "2666" de Roberto Bolaño (2017)
"In this dissertation, we propose that the experience of uprootedness is the axis that articulates the novels The Savage Detectives and 2666, by Roberto Bolaño. In both novels Bolaño problematizes this experience in its motifs, in the construction of the stories, in the delineation of the characters and the fictional spaces, and in the resources of the writing. The resources that make the writing tends to uprootedness are, among others, the fragmentation, the ellipsis, the digression, the multiplicity of narrators, the oscillations in focalization and style, the openness and suspense, the hybridity in the fictional genres, the flirtation with the fantastic and with science fiction, etc. These resources of the writing also produce uprootedness in the reader. Furthermore, the characters? identities are presented as fragmentary and disperse due to their constant movement (physical or mental), and the strangeness usually accompanies the construction of the stories and the fictional universes".-- Tomado del Formato de Documento de Grado.